2019
DOI: 10.3390/ijms20081965
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Binding Proteins HuB, HuC, and HuD are Distinctly Regulated in Dorsal Root Ganglia Neurons from STZ-Sensitive Compared to STZ-Resistant Diabetic Mice

Abstract: The neuron-specific Elav-like Hu RNA-binding proteins were described to play an important role in neuronal differentiation and plasticity by ensuring the post-transcriptional control of RNAs encoding for various proteins. Although Elav-like Hu proteins alterations were reported in diabetes or neuropathy, little is known about the regulation of neuron-specific Elav-like Hu RNA-binding proteins in sensory neurons of dorsal root ganglia (DRG) due to the diabetic condition. The goal of our study was to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…They found that HuR can bind to MMP-9, thus enhancing its stability, which promotes wound healing [ 171 ]. In diabetic neuropathy, a study demonstrated that, in diabetes, HuD downregulation and HuB upregulation occurred in dorsal root ganglia sensory neurons, which may be associated with mRNA involved in DRG neuronal excitability [ 173 ].…”
Section: Rna-rbps Interaction In Diabetes and Its Complicationsmentioning
confidence: 99%
“…They found that HuR can bind to MMP-9, thus enhancing its stability, which promotes wound healing [ 171 ]. In diabetic neuropathy, a study demonstrated that, in diabetes, HuD downregulation and HuB upregulation occurred in dorsal root ganglia sensory neurons, which may be associated with mRNA involved in DRG neuronal excitability [ 173 ].…”
Section: Rna-rbps Interaction In Diabetes and Its Complicationsmentioning
confidence: 99%
“… 2 , 14 - 16 HuD E-1 antibody binds to the ELAV like RNA-binding protein 1, which localizes to the nucleoplasm, nucleoli and cytosol of neurons. 17 , 18 DAPI is a small molecule that binds strongly to adenine–thymine rich regions of double-stranded DNA and localizes to the nucleus of any DNA-containing cell. 19 …”
Section: Resultsmentioning
confidence: 99%
“…This result agree with finding reported by Mostafavinia et al, 2016 [14] whose reported STZ to be considered as one of the most used diabetogenic compound for inducing diabetes in experimental animal models. Many reports indicated that STZ is capable of producing mild to severe types of diabetes that vary according to the selected dose, strain, and age of animals, nutritional status, and route of administration, along with other factors [15]. Moringa oleifera have been shown to have glucose lowering effect in hyperglycemic streptozocin induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%